Spain : Financial Sector Assessment Program; Technical Note; Stress Testing Methodology and Results. (IMF Staff Country Reports; Country Report, 2006)
This report presents a description of the stress test exercises for Spain's banking and insurance systems. The exercises were carried out in the context of the Financial Sector Assessment Program with the aim of assessing the resilience of the financial system to key risks. It describes the coverage of the exercises, the risks considered, the magnitude of the shocks to the risk factors, the models and instruments, and the results. It presents the stress test methodology and also the stress tests for the banking system and insurance.